Pengembangan Media Pembelajaran Sains Berbasis Augmented Reality untuk Kesiapsiagaan Penanggulangan Gempa di Taman Kanak-Kanak Qatrinnada di Kota Padang - Riska Armely; Yaswinda; Nenny Mahyuddin; Dadan Suryana (Jurnal Penelitian Pendidikan IPA, 2025)
This study was motivated by the low level of knowledge and skills among early childhood students in earthquake mitigation, partly due to uninteresting learning media and a low level of integration of the latest technology. The aim of this study was to develop augmented reality-based science learning media to improve earthquake mitigation preparedness among early childhood students. The research employs the R&D Gall, Gall, and Ball development model with nine stages, involving validation by three experts (content, media, and instruments) and a pilot test with participants from Group B of Qatrinnada Kindergarten in Padang City. Data were collected through observation, questionnaires, and documentation, then analyzed using validity, practicality, effectiveness, N-gain, and paired sample t-test analyses. Validation results showed high validity for the material (89.23%) and instruments (86%), and validity for the media (76%). The media was deemed highly practical (92.30%) and provided knowledge improvement with moderate N-gain values for the small class (0.69) and large class (0.58). The t-test revealed a significant difference between pretest and posttest scores (sig. 0.000 < 0.05). Therefore, the augmented reality-based science learning media developed is effective in enhancing earthquake mitigation readiness among young children.